(3EQTGO GdCPgGf Edi CMcGe GdEjeGfs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3CMeO Hf eMeO gGTe GdRhj GdTgjQ HNhTfhjSs)
(3ChdgG (B:s
(3cJGH GdeJGLQ hajg ebGUO GdChd aj GdebOeGJ hajg eWdHGf GdChd(B: (3aj CbSGegG hJfbSe HGfbSGe GdCMcGe GdNeSI(B: (3aGdhGLH efgG(B: (3eG GVWQ GdEfSGf Edjg aj GdeHGM(B.s
(3BNQgG (B:s
... (3hjSJhaj GdOjI aj GdNWC hTHgg hdjS dY GdYah YfgG heY JYOO GdLfGjGJ jJYOO GdOjGJ hEf GJMO GdLGfj hdh SQJ LfGjGJg hdh bJd bHd (B... (3JOGNdJ agPG NdGUI eG CaOfGg aj gPG GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2/ 227s
(3GdPQjYI (B1\2509s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis